Do plant extracts promote wound healing by activating the MAPK and Akt signaling pathway? - Michalak, Monika
The data are the result of the Miniatura 8 project and include preliminary studies of the biological activity of extracts obtained from selected plant species from the Lamiaceae family: Hyssopus officinalis and Marrubium vulgare, and Asteraceae: Grindelia robusta and Tanacetum parthenium, on two cell lines: keratinocytes HaCaT and fibroblasts BJ. Evaluation of the effect of the tested extracts was determined by their influence on signal transduction pathways - Akt and MAPK (ERK1/2, JNK, p38 kinase).